STRATEGIES FOR INTERNATIONAL ENTERPRISE COMPETITION - Eugeniusz Michalski (Polityki Europejskie, Finanse i Marketing)
The main aim of this paper is analyzed the role, importance and methodology for creating the strategies for international competition, as well as the ways of implementing and evaluating the selected strategies. This is done by applying exploratory, descriptive and casual methods to outperform competitors and determine the scope of an enterprise’s engagement in international business. The article examines forces and steps of planning, implementing and evaluating a business strategy. Enterprises must recognize and compare the factors that compose foreign environments, especially the state and local governmental politics, legal regulations, economic and financial forces, cultural differences, business ethics, technological development, infrastructure, natural resources protections, sociological and demographic issues. Three competitive strategies have been distinguished: cost leadership, differentiation and focus. Virtues of M. Porter’s five forces model: threat of new entry, competitive rivalry, supplier power, buyer power and threat of substitutes have been considered. The selection of the target markets and recognizing customers preferences belong to the most important tasks of strategic planning. An enterprise can select three levels of international involvement: passive participation, active involvement and taking the international position. Foreign countries impose barriers on international trade, but international agreements facilitate healthy competition.